The effect of propolis produced by Apis mellifera as a nutritional supplement on the expression level of NF-κB and LC3 anti-inflammatory immune genes in Iraqi Hamdani sheep - Mohsin Ali Ahmad (Journal of Kerbala for Agricultural Sciences, 2025)
This research aimed to measure the expression levels of the genes LC3 and NF-ĸB in Hamdani sheep blood that were fed with Apis mellifera propolis. Propolis, a bee product, has been utilized for centuries due to its numerous biological advantages. It was incorporated into their daily diet for six weeks. Propolis is well-known for its antimicrobial, anti-inflammatory, and immune-modulating effects in both animals and humans. The propolis was introduced to the diet every two weeks in quantities of 2, 3, and 4 grams. Following this, blood samples were collected from these 10 sheep biweeklies, and on the same day, RNA was extracted in the lab and converted into cDNA. The expression levels of the genes LC3 and NF-ĸB were assessed using a Real-Time PCR machine, and the ΔΔCt values were calculated based on reference gene expression. The gathered data were analyzed using the GraphPad software, revealing that the expression of the target genes increased when compared to the control data, with the optimal amount of bee propolis additive being 4 grams per day.